Effectiveness of Using Digital Technology-Based Learning Media in Increasing Student Motivation at State Elementary School 012 Ujung Batu III Rokan Hulu - Wahyudi, Sri; Lubis , Adyanata; Jufri; Chandra, Detri Amelia (Journal of ICT Applications System, 2023)
This research aims to explore the effectiveness of using technology-based digital learning media, particularly video media, in enhancing students' motivation in religious education in the fourth grade of SDN 012 Ujung Batu III. The research method used was direct observation with a qualitative approach. The results of the research indicate that the use of video media in religious education is effective in increasing interest, active participation, and an engaging learning environment. In the context of religious education in the fourth grade of SDN 012 Ujung Batu III, the use of technology-based digital learning media has a significant positive impact on students' motivation and learning achievement. The recommendations of this research emphasize the importance of teachers using video media and interactive learning methods to maintain student motivation and create an interesting and inspiring learning environment.